Aprotinin does not Impair Vascular Function in Patients Undergoing Coronary Artery Bypass Graft Surgery - Tolkmitt, Josephine; Brendel, Heike; Zatschler, Birgit; Brose, Stefan; Brunssen, Coy; Kopaliani, Irakli; Deussen, Andreas; Matschke, Klaus; Morawietz, Henning (Hormone and Metabolic Research, 2023)
Bleeding is a major complication in coronary artery bypass graft surgery. Antifibrinolytic agents like serine protease inhibitor aprotinin can decrease postoperative bleeding and complications of cardiac surgery. However, the effects of aprotinin on vascular function are not completely elucidated. We compared the ex vivo vascular function of left internal mammary arteries from patients undergoing coronary artery bypass graft surgery with and without intraoperative application of aprotinin using a Mulvany Myograph. Human internal mammary arteries were treated with aprotinin ex vivo and tested for changes in vascular function. We analyzed the impact of aprotinin on vascular function in rat aortic rings. Finally, impact of aprotinin on expression and activity of endothelial nitric oxide synthase was tested in human endothelial cells. Intraoperative application of aprotinin did not impair ex vivo vascular function of internal mammary arteries of patients undergoing coronary artery bypass graft surgery. Endothelium-dependent and -independent relaxations were not different in patients with or without aprotinin after nitric oxide synthase blockade. A maximum vasorelaxation of 94.5%±11.4vs. 96.1%±5.5% indicated a similar vascular smooth muscle function in both patient groups (n=13 each). Long-term application of aprotinin under physiological condition preserved vascular function of the rat aorta. In vitro application of increasing concentrations of aprotinin on human endothelial cells resulted in a similar expression and activity of endothelial nitric oxide synthase. In conclusion, intraoperative and ex vivo application of aprotinin does not impair the endothelial function in human internal mammary arteries and experimental models.
Keywords: aprotinin; coronary artery bypass graft surgery; endothelial cells; nitric oxide; vascular function